ELITE WOMEN IN EARLY MODERN CATHOLIC EUROPE ([S.l.])
1 online resource
Keywords: Elite Women in Early Modern Catholic Europe offers a new look at early modern Catholic Europe through the lens of the diverse experiences of elite women, using a historiographical approach to analyze women's roles through changing political, social, and cultural contexts. Through novel practices and broad social networks, distinguished women assumed prominent roles, from queens and princesses, to aristocrats and great nobles, to women of faith and religion. As the Counter-Reformation and the transition toward Enlightenment ideology swept France, Spain, and Italy, literacy and education became more accessible to upper-class women, who began to create new traditions in place of the old ways that were falling short. The case studies in this volume, ranging from the seventeenth to early nineteenth centuries, uncover the ways in which women were developing leadership skills and preserving status through participation in historical processes that affected real estate, the Church, and the social and family organization across Catholic Europe. This book is an ideal resource for students and researchers studying early modern women and Catholic Europe.